Literature Study: Transparency and Accountability of Local Government - Arfa Fachrulla; Sitti Namira Hasanuddin; Tuti Dharmawati (PT. Banjarese Pacific Indonesia, 2024)
This study examines the process of preparing financial statements for Regional Work Units (Regional Work Units, SKPD) using an accrual-based accounting approach in accordance with Government Regulation No. 71 of 2010. The discussion focuses on the complete accounting cycle, from the opening balance sheet to the final financial statements. The methodology used includes literature review and best practice analysis, using illustrative data. The results emphasize the importance of a comprehensive understanding of the SKPD accounting cycle to produce accurate financial statements that adhere to established standards. Furthermore, this study reviews existing literature on transparency and accountability in local governments, identifies challenges and opportunities, and offers recommendations to enhance these aspects. By understanding the accrual-based accounting process and advancing transparency and accountability efforts, it is expected that local government financial statements will become more meaningful, reliable, and supportive of better decision-making processes for stakeholders.